Deteksi Kebuntingan pada Kambing Lokal Menggunakan Metode Punyakoti dengan Konsentrasi Urin dan Aquades Berbeda pada Pertumbuhan Biji Kacang Hijau - Ridhani, Ahmad; Riyadhi, Muhammad; Wahdi, Anis (www.ulm.ac.id, 2025)
The objective of this study was to determine whether the Punyakoti method can be used to detectpregnancy in goats by modifying the amount of distilled water (aquadest) added to goat urine toobserve growth inhibition in mung bean seeds. This study was designed using a CompletelyRandomized Design (CRD) with four treatments and six replications. The treatments involveddifferent concentrations of aquadest added to the urine: P1 (1:4), P2 (1:8), P3 (1:12), and P4(1:12) using urine from non-pregnant goats. The observed variables were the germination of eachseed and the length of the sprouts on the fifth day. Data were analyzed using Analysis of Variance(ANOVA), and if significant or highly significant differences were found, Duncan’s MultipleRange Test (DMRT) was applied. The ANOVA results showed a significant difference in the sprout length of mung beans due to the variation in goat urine and aquadest concentrations.Treatment P1 (2.36 cm) produced significantly shorter sprouts (P<0.05) compared to P2 (5.75cm), P3 (8.38 cm), and P4 (12.02 cm). The shorter sprout length in treatment P1 is likelyinfluenced by the higher concentration of urine diluted with aquadest. In treatment P4, mung beansprouts were longer, as this treatment used urine from non-pregnant goats. As a comparison,treatment P3, which used the same urine-to-aquadest ratio as P4, showed different sprout lengthsbecause the urine came from pregnant goats. This difference may be due to the higherconcentration of abscisic acid (ABA) in the urine of pregnant goats. Based on the results, it canbe concluded that the Punyakoti method can be used as an alternative method for detectingpregnancy in goats with 100% accuracy. The 1:4 concentration was the most effective, as itshowed the clearest growth inhibition compared to the 1:8 and 1:12 concentrations. Thisdemonstrates that different concentrations of aquadest affect the degree of growth inhibition inmung bean seeds